Genetic diversity analysis for moisture stress adaptive and quality traits in bread wheat (Triticum aestivum) - KALLESH, D T; SINGH, G P; SINGH, ANJU M; AHLAWAT, ARVIND; SHARMA, R K (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted to work out the genetic divergence for yield, morpho-physiological and quality traits in timely sown restricted irrigated and rainfed conditions. In the pooled analysis, cluster IV and V had 33 genotypes each and cluster III contained 29 genotypes, while cluster VI had 22 genotypes. Eighteen and 15 genotypes were included in cluster I and II, respectively. Maximum intra-cluster distance was reported in cluster III followed by VI, II, I and IV and minimum intra- cluster distance was found for cluster V. Genotypes included in III, VI and II revealed maximum diversity among themselves. Highest inter-cluster distance was observed between cluster II and III followed by I and III, I and VI. Moderate inter-cluster distance was noticed between II and IV in the pooled analysis. Parentage of 150 genotypes revealed that genotypes were belonging to different eco-geographical areas were included in the same cluster. This indicated that there is no association between clustering pattern and eco- geographical distribution of genotypes.